Little by little - Stewart, Amber; Marlow, Layn (New York : Orchard Books, 2008)
Little Otto the Otter can do a lot of things except swim, but with the help of his sister and lots of practice, Otto finally overcomes his fears.
2.4
K-3
Keywords: Swimming -- Juvenile fiction; Determination (Personality trait) -- Juvenile fiction; Self-confidence -- Juvenile fiction; Otters -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Swimming -- Fiction; Determination (Personality trait) -- Fiction; Self-confidence -- Fiction; Otters -- Fiction; Brothers and sisters -- Fiction; Swimming -- Fiction; Determination (Personality trait) -- Fiction; Self-confidence -- Fiction; Otters -- Fiction; Siblings -- Fiction; Swimming -- Fiction; Determination (Personality trait) -- Fiction; Self-confidence -- Fiction; Otters -- Fiction; Brothers and sisters -- Fiction